Skeletal Muscle Hyperemia: A Potential Bridge Between Post-exercise Hypotension and Glucose Regulation - Pellinger, Thomas K.; Emhoff, Chi-An W. (Frontiers in Physiology, 2022)
For both healthy individuals and patients with type 2 diabetes (T2D), the hemodynamic response to regular physical activity is important for regulating blood glucose, protecting vascular function, and reducing the risk of cardiovascular disease. In addition to these benefits of regular physical activity, evidence suggests even a single bout of dynamic exercise promotes increased insulin-mediated glucose uptake and insulin sensitivity during the acute recovery period. Importantly, post-exercise hypotension (PEH), which is characterized by sustained post-exercise skeletal muscle vasodilation that is not completely off-set by a still elevated cardiac output, appears to be blunted in those with T2D compared to their non-diabetic counterparts. In this short review, we describe research that suggests the sustained post-exercise vasodilation observed in PEH sub-serves glycemic regulation following exercise in both healthy individuals and those with T2D. Furthermore, we discuss the interplay of enhanced perfusion, both macrovascular and microvascular, and glucose flux following exercise. Finally, we propose future research directions to enhance our understanding of the relationship between post-exercise hemodynamics and glucose regulation in healthy individuals and in those with T2D.